ortho-Carbaborane Derivatives of Indomethacin as Cyclooxygenase (COX)-2 Selective Inhibitors - Scholz, Matthias (2012)
A series of novel indomethacin analogues with carbaboranes as three-dimensional substitutes for the chlorophenyl ring have been prepared. Their cyclooxygenase (COX) inhibition and enzyme selectivity has been tested and compared to the corresponding adamantyl analogues. Surprisingly, only the ortho-carbaborane derivatives were active compounds. Preliminary biological studies gave an interesting insight into the validity of employing carbaboranes as pharmacophores.